Mitochondria and copper homeostasis in plants - García, Lucila (2014)
Copper (Cu) and other transition metals are essential for living organisms but also toxic when present in excess. To cope with this apparent paradox, organisms have developed sophisticated mechanisms to acquire, transport and store these metals. Particularly, plant mitochondria require Cu for the assembly and function of cytochromec oxidase (COX), the terminal enzyme of the respiratory chain. COX assembly is a complex process that requires the action of multiple factors, many of them involved in the delivery and insertion of Cu into the enzyme. In this review, we summarize what is known about the processes involved in Cu delivery to mitochondria and how these processes impact in Cu homeostasis at the cellular level. We also discuss evidence indicating that metallochaperones involved in COX assembly play additional roles in signaling pathways related to changes in Cu and redox homeostasis and the response of plants to stress. We propose that cysteine-rich proteins present in the mitochondrial intermembrane space are excellent candidates as sensors of these changes and transducers of signals originated in the organelle to the rest of the cell.